Service-Aware Resource Allocation Design of UAV RAN Slicing - Cho, Jun Woo; Yang, Peng; Quek, Tony Q.S.; Kim, Jae Hyun (International Conference on ICT Convergence, 2020)
Unmanned Aerial Vehicles (UAVs) can be used in a radio access network (RAN) to expand communication range and connectivity and support innovative services in the 5G ecosystem. In such systems, UAV RAN slicing can be applied in terms of network slicing to meet the quality of service (QoS) requirements. In this paper, we propose a resource allocation algorithm for UAV RAN slicing based on the 5G frame structure when system bandwidth is limited. Our proposed algorithm selects a type of slot to satisfy service type and to improve resource efficiency. Performance results show that each slice is satisfied with the required QoS.
Keywords: Communication range; G frames; Network slicing; Qualityof-service requirement (QoS); Resource allocation algorithms; Resource efficiencies; Service-aware; System bandwidth; 5G; Network slicing; RAN slicing; Resource allocation; UAV